Evaluation of the functional capacity of elderly women with arthralgia who practice water aerobics and registered in the multidisciplinary care program for elderly health (Research, Society and Development, 2020)
Musculoskeletal complaints are the most prevalent among the elderly. Osteoarthritis is a chronic, multifactorial disease that leads to progressive functional disability. Treatment must be multidisciplinary to assist in functional, mechanical and clinical improvement. The objective was to evaluate the benefits of water aerobics in elderly women, diagnosed with osteoarthritis and who had been exercising for over a year at Multidisciplinary Care Program for Elderly Health. The study was clinical with primary and quantitative information. The questionnaire was answered by 35 elderly women registered and classified in the modalities: water aerobics, walking and not doing physical exercise. The results showed that the functional capacity of the elderly women was considered mild in HAQ and 74.3% had a diagnosis of arthritis. Among the group, 85.7% of the elderly women practiced water aerobics as a physical exercise, with a more prevalent frequency of twice a week and 95.8% of them reported decreased arthralgia. We conclude that water aerobics can be recommended to reduce arthralgia and improve the functional capacity of the elderly, improving the HAQ assessment and promoting greater independence in daily activities.